2015
DOI: 10.1136/annrheumdis-2015-eular.5030
|View full text |Cite
|
Sign up to set email alerts
|

FRI0288 Role of Physical Exercice Program in Patients with Osteoporosis

Abstract: BackgroundHaving an important negative impact not only on bone health, but also on general health, with serious consequences as the fragility fractures, osteoporosis had became a major public health problem, with high socio-economic cost.ObjectivesThe aim of this study was to assess the efficacy of a 6 months ambulatory exercise program on functional status and quality of life in women with postmenopausal osteoporosis.MethodsThe randomized, controlled, observational study included 81 patients with postmenopaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Quality improvement initiatives targeting the health system include interventions with positive or negative financial incentives directed at clinicians (eg, linked to adherence to some process of care or achievement of some target outcome), positive or negative financial incentives directed at patients, or system-wide changes in reimbursement systems included (citations in eReferences in the Supplement), with a total of 159 910 participants (mean age 78.1 years; 74% women). Two included studies were available only as conference abstracts, 35,36 and 14 other studies were identified by scanning reference lists of included studies and relevant reviews. [37][38][39][40][41][42][43][44][45][46][47][48][49][50] Author Contact…”
Section: Health System Levelmentioning
confidence: 99%
“…Quality improvement initiatives targeting the health system include interventions with positive or negative financial incentives directed at clinicians (eg, linked to adherence to some process of care or achievement of some target outcome), positive or negative financial incentives directed at patients, or system-wide changes in reimbursement systems included (citations in eReferences in the Supplement), with a total of 159 910 participants (mean age 78.1 years; 74% women). Two included studies were available only as conference abstracts, 35,36 and 14 other studies were identified by scanning reference lists of included studies and relevant reviews. [37][38][39][40][41][42][43][44][45][46][47][48][49][50] Author Contact…”
Section: Health System Levelmentioning
confidence: 99%
“…Research has shown that after exercise intervention, individuals with OP demonstrate significant improvements in quality of life, pain scores, and balance performance ( Marcu et al, 2015 ; FILIPOVIĆ et al, 2021 ), but there is still controversy regarding changes in BMD ( Wei et al, 2015 ). BMD is an important indicator for diagnosing individuals with OP ( Sugerman, 2014 ), and increasing BMD through exercise is crucial for preventing and treating OP ( Gregson et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%